Effect of annealing temperature on the rheological property of ZnO/SiO2nanocomposites for Enhanced Oil Recovery - Mudassir Hassan, Y. (Elsevier Ltd, 2021)
The advanced process of recovering the trapped oil from the reservoir is known as Enhanced Oil Recovery (EOR), which involves the injection of foreign fluids to manipulate the reservoir's petrophysical properties. Nanoparticles in this regard have shown significant effects on various EOR parameters, such as interfacial tension and sweep efficiency. However, the composites of different nanoparticles have been reported to have shown exceptional effects over bare single nanoparticles (NPs) because of the synergy actions concerning measures of improving their rheological properties. In this work, Zinc oxide/Silicon dioxide (ZnO/SiO2) nanocomposites were synthesized via a Sol-gel method and annealed at different temperatures (400 and 600Â°C). The chemical interaction, crystal structures, morphology, and composite formation were studied via Fourier-Transform Infrared Spectroscopy (FTIR), X-Ray diffractometer (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Energy dispersed X-ray (EDX) respectively. The result shows that the chemical interactions between the ZnO and amorphous SiO2were confirmed by the presence of the characteristic functional group bands, and the establishment of the chemical bond in Zn-O, and Si-O on the surface of the composite materials. From the XRD analyses, the crystal size of the ZnO/SiO2composite materials significantly increased with an increase in temperature whereas the morphological size undergoes a reduction by increasing temperature as shown by FESEM. The rheological property (viscosity) of the ZnO/SiO2nanocomposites was investigated and the outcome has revealed that the viscosity of the composite material increases with an increase in annealing temperature which consequently could serve as a basis to overcome the viscous fingering and facilitates the oil displacements in EOR. Â© 2021 Elsevier Ltd. All rights reserved.